Defending in the handball game (junior level) - Mihaila, I.; Stanescu, S. (Science, Movement & Health, 2019)
Problem statement. The new trends in technical, strategic, physical handball development require more and more features of players who need to be faster, more dynamic, versatile in both attack and defense, technically skilled, capable of playing from any position, have an excellent perception of play. The aim of the paper is to analyze the importance of defense systems in handball games. At national level, the defensive game concept follows on-the-ground application of basic features and principles to ensure greater efficiency of game systems. In this sense, it is intended to create a supranumeric agglomeration in the ball area, to increase the individual aggression and implicitly the entire defense system. The evolution of the defense, as well as its modern technical means, allow through the increase of individual aggressivity to neutralize the shot. Current research shows the level of force and the number of throws at the goal as criteria for determining the level of training of a player and team.This aspect led to a new defense orientation -the blocking of the attackers throwing at the gate of Line II. Thus, defense has become advanced, with strong, dynamic players. It is revealed that 75% of the time of play is dedicated to defense. The current defenses are very organized and very aggressive, with great cohesiveness and cooperation of the goalkeepers with the defending players. Radical changes in defense systems occur in matches depending on the opponent and the situation of the game. The zone defense system is most commonly used by European teams, while non-European teams opt for offensive defense to counteract morphological disability. Conclusions. The defende of today must be a universal athlete with field mobility to defend man to man, increasing interaction with teammates, who actively participate in individual and group blockages.